Determinación del mejor método de pelado y secado del banano musa sapientum para la obtención de harina - Ruiz Quezada, Marcos Augusto (2015)
This research consisted in determining the best method for peeling and drying bananas (Musa sapientum) in order to obtain banana flour. It was conducted with seven treatments with three forms of peeling including: hot water, rice water and peeled normally with values ranging from 10.65 to 21.75 (sg), corresponding to the lowest average at T 6 which consisted of making a scalded with direct steam at 94 ° C for 3 min over the washed bananas, while hot were peeled and greater than T1 which was based on the use of rice water to be made at the time of executing the peeling prevented the latex from sticking in to my hands. Quickly proceeded to slice the bananas in three different ways: knife, slicer and grater, in which it was found that the mean varies within the range of 12.875-34.450 (sg), concerning the highest average treatment and the value shorter banana flour from treatment 6, which was based on thin knife cut for smaller pieces that can be shaped into cubes or slices. This step is necessary to ease the drying process, and had to be done in two ways, with a dehydrator machine and using awnings across the sun, but it was not right because the highest microbial loads treatments 2 -5 was obtained in others they are within the parameters of the standard 0616 INEN. In the fresh fruit banana flour conversion results indicated no statistical significance due to the very small range of 5.80 - 6.50 of statistical significance Other parameters are the bromatological assessment consisting of analyzes of proteins, fat, pH, and moisture. Most of the analysis had no significant differences when comparing the seven treatments; taking into account the new rules of health regulations for food labeling in Ecuador. No wonder the price of banana flour was established this result gave the highest value of 2.61 a kilogram, to get the retail price obtained the average of all values, this gave us 2.15 dollar per kg banana flour, it should be noted that the price only take into account the cost of production without taking the balance of investment, plus these prices were obtained with laboratory conditions, but these values can be lowered using industrial machines to improve flour production.